EFEKTIVITAS MODEL PROBLEM BASED LEARNING BERBANTUAN LKPD TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS 5 DI SD 1 UNDAAN KIDUL - Rahmita Cahya Putri; Septina Rahmawati; Devy Aufia Abshor (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is based on the application of an ineffective learning model, which has resulted in many students failing to meet the Minimum Completeness Criteria (KKM). This research aim to determine the effectiveness of the Problem Based Learning (PBL) model assisted by Student Worksheets (LKPD) on the mathematics learning outcomes of class 5 students at SD 1 Undaan Kidul. This research uses a quantitative approach method with a Quasi Experimental Design, specifically the Nonequivalent Control Group Design. The sampling technique uses total sampling. The data collection techniques in this research used pretest and posttest assessments administered to class 5B as the experimental class and class 5A as the control class. The data analysis techniques used are the Shapiro-Wilk normality test, homogeneity test, t-test, and N-Gain test. The research hypothesis states that there is a difference in learning outcomes between students who use the Problem Based Learning model assisted by LKPD and those who use the conventional model. Based on the results, the mean N-Gain for the experimental class was 61.18%, which is categorized as quite effective. Meanwhile, the mean N-Gain for the control class was 29.99%, which is categorized as failed. It was concluded that the use of the Problem Based Learning model assisted by LKPD is quite effective in increasing the mathematics learning outcomes of class 5 students at SD 1 Undaan Kidul.